Enhancing Social Maturity: A Study on the Effectiveness of TGT Method in Primary Schools - Anggraeni, Sri Wulan; Alpian, Yayan; Prihamdani, Depi; Fahrudin, Riki (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2025)
This study addresses the challenge of social immaturity among elementary school students by exploring the social benefits of the Teams Games Tournament (TGT) Cooperative Learning Method. The research involved 21 third-grade students from Karyamakmur III Elementary School, using a one- group pretest-posttest experimental design. Data were collected through questionnaires measuring aspects of social maturity and analyzed using descriptive and inferential statistical methods. The results revealed a significant improvement in students' social maturity, with the average score increasing by 0.54 points, from 13.5 in the pretest to 14.04 in the posttest, supported by a significance value of 0.000 < 0.05. The TGT method proved effective in fostering teamwork, positive interactions, and healthy competition, helping students achieve shared learning goals. The study concludes that TGT is an effective strategy for enhancing social maturity in elementary education. Teachers are encouraged to integrate TGT into classroom activities to strengthen students' interpersonal skills and create a more collaborative learning environment.